Innovative Automatic Clothes Dryer with Sensor Technology - สาระวัน สาธิดา; Phetkhiri, Apisit; Somaket, Sutee (Science Technology and Innovation Journal, 2021)
The organizing committee has created a Clothes dryer in the residence the purpose is to fix the problem of clothes not drying due to rain. The inappropriate place for drying clothes and to reduce the drying time The proposed system has the following important equipment: Arduino Uno R3 miniature control system, heating coil, temperature sensor, humidity sensor the clothes dryer has the following working principle. Only the clothes that have been spun are to be hung in the tumble dryer. Close the tumble dryer and turn it on to start using it. heating coil and the temperature and humidity sensor will start working immediately. When the temperature inside the tumble dryer is higher than 60°C, the system will cut off the heating coil circuit to reduce the temperature inside the cabinet. When the temperature inside the cabinet drops to 50 degrees Celsius the heating coil will work again. At the same time, when the humidity sensor inside the tumble dryer measures the humidity below 40 percent, the system will stop the heating coil immediately as the laundry is completely dry. Tests show that it takes 53 to 85 minutes to finish drying. And there is an electric charge of 3.08 to 5.08 baht per dryer. As a result, the dryer can save costs. Solve problems and knowing the length of time to finish drying clothes makes drying clothes no longer a problem.